2019
DOI: 10.1016/j.metabol.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Leptin trajectories from birth to mid-childhood and cardio-metabolic health in early adolescence

Abstract: Objectives: Leptin is a hormone produced by adipose tissue that promotes satiety, and some evidence suggests that greater early life leptin exposure prevents excessive adiposity gain in later life. However, few studies have analyzed dynamic changes in leptin throughout childhood in relation to later cardio-metabolic health. Our study aims to identify distinct leptin trajectories in childhood, and to examine their associations with cardio-metabolic outcomes in adolescence.Methods: Among children in the Project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Interestingly, it was previously reported that neonatal leptin levels might be associated with growth trajectories and childhood BMI [48,49], but other studies showed that both lower and higher leptin levels are associated with weight gain [50][51][52][53][54][55][56][57]. Nevertheless, although the association between neonatal leptinemia and childhood growth and adiposity (e.g., weight gain, BMI, and/or obesity) has been previously reported [48][49][50][51][52][53][54][55][56][57][58], the impacts of altered neonatal leptin levels on fat distribution during childhood still need to be clearly defined.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, it was previously reported that neonatal leptin levels might be associated with growth trajectories and childhood BMI [48,49], but other studies showed that both lower and higher leptin levels are associated with weight gain [50][51][52][53][54][55][56][57]. Nevertheless, although the association between neonatal leptinemia and childhood growth and adiposity (e.g., weight gain, BMI, and/or obesity) has been previously reported [48][49][50][51][52][53][54][55][56][57][58], the impacts of altered neonatal leptin levels on fat distribution during childhood still need to be clearly defined.…”
Section: Discussionmentioning
confidence: 96%
“…There is a high degree of tracking for BMD [53] and it was therefore reasonable to assume that this was the case for the bone-active substances and BTMs, which was also found. To our knowledge there are only a few reports on tracking of individual bone related substances [54, 55], but none where these substances and the BTMs are evaluated together. This high degree of tracking makes it likely that our cross-sectional results are valid for bone metabolism over time and not only represent findings from a single measurement.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, leptin can impel the hepatic stellate cell activation and liver fibrosis, control the energy balance, and suppress appetite [91]. Increased levels of leptin were found in subjects with increased body fat and cardiometabolic disorders [92]. Authors noted in a cross-sectional study that NAFLD patients have lower adiponectin levels, higher serum leptin levels, and higher leptin-to-adiponectin (L/A) ratio [93].…”
Section: Adipokinesmentioning
confidence: 99%